Feasibility and first results of a prospective cohort study to investigate cisplatin-associated ototoxicity amongst cancer patients in South Africa - Paken J; Govender CD; Pillay M; Ayele BT; Sewram V (BioMed Central Ltd, 2021)
Background Cervical cancer, one of the most common cancers affecting females in South Africa, commonly requires a cisplatin-based-treatment regimen, which has been associated with ototoxic side effects. However, cisplatin-associated ototoxicity is largely under-reported in South Africa, despite its impact of hearing loss having serious overt ramifications on the quality of life of these patients. Hence, a prospective cohort study was undertaken to assess the audiological changes in female cervical cancer patients receiving cisplatin therapy. Objective To present details of the feasibility study and initial results on hearing patterns in cervical cancer patients receiving cisplatin chemotherapy. . Methods Fifty cervical cancer patients commencing with cisplatin chemotherapy underwent audiological assessments at a hospital in South Africa at various time intervals. Assessments included case history, otoscopic examination, immittance audiometry, pure tone audiometry (including high-frequency audiometry), speech audiometry, and distortion product otoacoustic emission testing. Data analysis involved the use of descriptive statistics and the Cochran-Armitage trend test for a linear trend in proportions. Results Fifty participants, aged between 32 and 79 years (Mean: 53 years; SD = 11.00), were recruited. Clinical findings revealed an incidence of 100% ototoxic hearing loss at the one-month post-treatment, i.e., 98% after three cycles of cisplatin and 2% at one-month post-chemotherapy. Sensorineural hearing loss and high-frequency tinnitus were most common. Deterioration in hearing thresholds was more evident in the extended high-frequency range, with the number of “no-responses,” from 11,200 Hz to 20,000 Hz, increasing with each successive audiological evaluation. This study further indicated that recruitment and follow-up of study participants within a limited resource setting are possible. However, cognizance must be given to a multidisciplinary approach and constant engagement with participants through regular contact either telephonically or via a short-message-system. Conclusion Exposure to cisplatin treatment contributed to hearing loss in females with cervical cancer, highlighting the need for ototoxicity monitoring during chemotherapy treatments. Furthermore, the results indicate that it is possible to conduct prospective cohort studies, using a multidisciplinary approach in limited-resource environments with appropriate planning and training strategies, as this study was able to achieve its aim successfully.
(c) 2021 The Author/s
Keywords: Cervical Cancer; Cisplatin; Ototoxicity; South Africa; Adult; Aged; Antineoplastic Agents; Cisplatin; Cohort Studies; Feasibility Studies; Female; Humans; Male; Middle Aged; Neoplasms; Ototoxicity; Prospective Studies; Quality of Life; South Africa